Use of Vinegar as A Candidate Substitute Of Acetic Acid (CH3COOH) in The Rivalta Test Method in Diagnosis Feline Infectious Peritonitis (FIP) Domestic Cat - Zuraidawati, Zuraidawati; Dewi, Maryulia; Syah, Nanda Yulian; Zamzami, Rumi Sahara (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
This study aims to test the samples of abdominal fluid from cats suspected of having FIP by using vinegar as a substitute for acetic acid in the rival method. Feline Infectious Peritonitis (FIP) is a viral disease that is not zoonotic, but is very fatal with an infectious prognosis in various types of cats and its transmitted orally. This study aims to determine the positive or negative results of FIP infection in cats. The diagnosis of FIP can be seen through clinical symptoms such as lack of appetite, diarrhea, weakness, dehydration (reaching 8%), Body Condition Score (BCS) 2, enlarged abdomen, and ultrasound results showing ascites and swollen kidneys. This study uses vinegar as a substitute for acetic acid in the rival method. The test was carried out experimentally in a laboratory. The research data were analyzed descriptively, the results of a positive FIP reaction were indicated by the presence of a cloudy jellyfish-shaped precipitate in the test tube.